Exploring Nursing Students’ Expectations on Preceptoring and Preceptorship Program: A Mixed Method Study - Rebecca Mathew; Judith Angelitta Noronha; Shalini Ganesh Nayak (Journal of Caring Sciences)
Introduction: This study addresses the imperative in contemporary nursing education to prepare students for diverse healthcare settings by exploring nursing students’ expectations and perceptions of preceptorship programs, emphasizing the role of evidence-based educational strategies. The research aims to bridge the existing literature gap and contribute valuable insights into strategically designing preceptorship programs aligned with nursing students’ needs, preferences, and aspirations, ultimately enhancing precepting practices and relationships within nursing education. Methods: Employing a sequential explanatory mixed method, 140 nursing students, from various colleges in the United Arab Emirates (UAE) participated in the study. A structured questionnaire, encompassing demographic information, a need assessment survey, and a survey on expectations on preceptors was administered. A focus group discussion was conducted to identify perceived barriers to the utilization of preceptorship practices in nursing colleges. Data analysis involved descriptive statistics, the chi-square test, exploratory factor analysis, and content analysis of the focus group discussion. Results: The majority of participants expressed a high need for a preceptorship program, providing empirical evidence to support the development of a nurse educator preceptorship program in colleges and institutes. Preceptorship was identified as a significant contributor to career growth and achievement for nursing students, serving as a valuable tool to establish professional competency throughout their careers. Conclusion: There is a complex demand and high expectations for the core role of nurse educators as preceptors in the field of nursing education. This pioneering study sheds light on the need and perception of nursing students for a preceptorship program in the nursing curriculum.